Law and jurisprudence on government organization, administration and officers (a source book on constitutional law, administrative law and public officers) - Martinez, Daniel T. (Quezon City : Central Lawbook, 1993)
2 Parts
Keywords: Administrative law -- Philippines; Public officers -- Philippines